Comparison Of Clinical Efficacy Of Combined Versus Monotherapy Of Oral Zinc And Probiotic In Pediatric Acute Diarrhoea At Benazir Bhutto Shaheed Teaching Hospital, Abbottabad - Anila Farhat; Asma Shaukat; Noman Sadiq (Journal of Bahria University Medical and Dental College, 2021)
Objective: Evaluation of effectiveness of zinc/ probiotics alone and in combination in children with acute diarrhoea. Place of Study: The study was conducted from May-Dec 2017 at Benazir Bhutto Shaheed Teaching Hospital Abbottabad. Methodology: Single centered, randomized controlled clinical trial was performed in 150 children of either sex (6 months -10 years) with acute diarrhoea having stool frequency of > 5semi liquid stools per day. Patients were divided into three groups with fifty children in each group on the basis of treatment modality given. Group A received zinc orally (1-2mg/kg/day for five days along ORS and/or IV fluids if required), Group B patients were given one to two sachets of probiotics /day (saccharomyces boulardii) according to age for five days + ORS and /or IV fluid while Group C was administered combination of zinc and probiotics for five days along with ORS and /or IV fluids. Response to treatment was determined on the basis of decrease in frequency of stools i.e. <3 formed stools /day after 72 hours of commencement of treatment. We have also studied the relationship between hygiene and food intake practices with the occurrence of diarrhoea in children. Results: Acute diarrhoea was found to be more prevalent in children with poor hygiene practices and using unboiled water. Among the treatment groups, at the end of 3rd day total of forty eight (96%) patients in group C had improved consistency of stools as well as decrease in diarrhoea frequency to less than three formed stools per day while in groups A and B thirty nine (78%) and sixteen (32%) patients respectively showed response to treatment in 72 hours.